2012
DOI: 10.1016/s1474-4422(12)70203-x
|View full text |Cite
|
Sign up to set email alerts
|

MRI profile and response to endovascular reperfusion after stroke (DEFUSE 2): a prospective cohort study

Abstract: Background It is uncertain if endovascular stroke therapy leads to improved clinical outcomes due to a paucity of data from randomized placebo-controlled trials. The aim of this study was to determine if MRI can be used to identify patients who are most likely to benefit from endovascular reperfusion. Methods Consecutive patients, scheduled to undergo endovascular therapy within 12 hours of stroke onset, were enrolled in a multi-center prospective cohort study. Aided by an automated image analysis software p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
704
4
21

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 722 publications
(750 citation statements)
references
References 26 publications
21
704
4
21
Order By: Relevance
“…18 In our study, patients with poor collateral status who did not recanalize had more infarct growth than did patients with poor collateral status who recanalized. Our results do not support the reperfusion injury hypothesis.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…18 In our study, patients with poor collateral status who did not recanalize had more infarct growth than did patients with poor collateral status who recanalized. Our results do not support the reperfusion injury hypothesis.…”
Section: Discussionmentioning
confidence: 45%
“…Similar to previous studies supporting the use of a "mismatch"-based para- digm on perfusion imaging, our study provides evidence for the use of a "CTA collateral assessment-based paradigm" in selecting patients for IAT. 18 We did not have data on every procedural time metric; approximately 30% of follow-up clinical data (mRS at 90 days) was ascertained by telephone. We were also underpowered to do a secondary analysis on the effect of time to recanalization on clinical outcomes stratified by collateral status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Furthermore, a recent study has suggested the value of perfusion imaging (PI) for selecting patients for IAT. 12 Despite the promise of MRI, there are few data concerning IAT outcomes after MRI-based selection. In most centers, patients are selected for intraveneous tPA and IAT on the basis of a CT scan.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate patient selection may thus prove paramount, and identification of a subpopulation most likely to benefit has been the subject of extensive inquiry. 1,2 While the precise profile of this target population remains to be conclusively defined, recent work has highlighted the potential strengths of stratification by using the ischemic penumbra formalism defining an irreversibly injured infarct core and putative penumbra of at-risk tissues. 1,3 Despite promising results, penumbral imaging has met with skepticism and inconsistent outcomes, particularly because the broad array of imaging and computational approaches and interpretive parameters has precluded formulation of generalizable conclusions.…”
mentioning
confidence: 99%